2011
DOI: 10.1007/s00705-011-1080-2
|View full text |Cite
|
Sign up to set email alerts
|

Pseudorabies virus in wild swine: a global perspective

Abstract: Suid herpesvirus 1 (SuHV1, syn. Aujeszky's disease virus [ADV] or pseudorabies virus [PrV]), which belongs to the family Herpesviridae, subfamily Alphaherpesvirinae, genus Varicellovirus is the causative agent of Aujeszky's disease (AD, pseudorabies), a notifiable disease, that causes substantial economic losses to the swine industry in countries, where AD is present. Members of the family Suidae (true pigs) are the only natural hosts for PrV, although the virus can infect numerous other mammals including rumi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
263
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 261 publications
(273 citation statements)
references
References 76 publications
7
263
0
3
Order By: Relevance
“…Despite the small sample size, our results confirmed that PrV infection is endemic in wild-boar populations in the study area, with antibody prevalence similar to that previously reported in Italy (Lari et al 2006) and Europe (Mü ller et al 2011). Eight years prior to our study, similar epidemiologic studies in the area had comparable results, demonstrating that PrV infection persists in wild boar populations (Corn et al 2004).…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Despite the small sample size, our results confirmed that PrV infection is endemic in wild-boar populations in the study area, with antibody prevalence similar to that previously reported in Italy (Lari et al 2006) and Europe (Mü ller et al 2011). Eight years prior to our study, similar epidemiologic studies in the area had comparable results, demonstrating that PrV infection persists in wild boar populations (Corn et al 2004).…”
Section: Discussionsupporting
confidence: 91%
“…Several studies and field observations indicate that PrV infection of wild boars results in low pathogenicity, indicating that the virus is attenuated in wild boars (Mü ller et al 2011). Studies carried out with the use of PrV isolates from the US and East Germany produced mild clinical symptoms in experimentally infected wild boars and domestic pigs Mü ller et al 2001).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations